Do Patients With Intersectional Disadvantage Have Poorer Outcomes From Osteoarthritis Management Programs? A Tapered Balancing Study of Patient Outcomes From the Good Life With Osteoarthritis in Denmark Program. Issue 1 (10th September 2022) - Peat, George; Yu, Dahai; Grønne, Dorte T.; Marshall, Michelle; Skou, Soren T.; Roos, Ewa M.
Abstract : Objective: To investigate whether adults with potential multiple social disadvantage have poorer outcomes following attendance in an osteoarthritis (OA) management program (OAMP), and if so, what might determine this result. Methods: Among consecutive knee OA attendees of the Good Life With Osteoarthritis in Denmark (GLA:D) OAMP in Denmark we defined a group with potential "intersectional disadvantage" based on self‐reported educational attainment, country of birth, and citizenship. Outcomes of this group were compared with GLA:D participants who were native Danish citizens with higher educational attainment. Outcomes were pain intensity, Knee Injury and Osteoarthritis Outcome Score (KOOS) quality of life subscale score, and the EuroQol 5‐domain instrument in 5 levels (EQ‐5D‐5L) score at 3 and 12 months. After data preprocessing, we used entropy balancing to sequentially control for differences between the groups in baseline covariates. Mean between‐group differences in outcomes were estimated by weighted linear regression. Results: Of 18, 448 eligible participants, 250 (1.4%) were nonnative/foreign citizens with lower education. After balancing for differences in baseline score and in administrative and demographic characteristics, they had poorer outcomes than higher‐educated native Danish citizens on pain intensity and EQ‐5D‐5L score at both follow‐up points (e.g., between‐group mean differences in pain visual analog scale [0–100] at 3 and 12 months: 3.4 [95% confidence interval (95% CI) –0.5, 7.3] and 6.2 [95% CI 1.7, 10.7], respectively). Differences in KOOS quality of life subscale score, were smaller or absent. Balancing for differences on baseline score, comorbidity, self‐efficacy, and depression had the greatest effect on reducing observed outcome inequalities. Conclusion: Outcome inequalities widened following OAMP attendance, particularly at longer‐term follow‐up, but the magnitude of differences was generally modest and inconsistent across outcome measures. Tailoring content to reduce outcome inequalities may be indicated, but improving access appears the greater priority.